Functional Development of the Octenol Response in Aedes aegypti - Bohbot, Jonathan D.; Durand, Nicolas F.; Vinyard, Bryan T.; Dickens, Joseph C. (Frontiers in Physiology, 2013)
Attraction of female Aedes aegypti mosquitoes to 1-octen-3-ol (octenol), CO2, lactic acid or ammonia emitted by vertebrate hosts is not only contingent on the presence of odorants in the environment, but is also influenced by the insect’s physiological state. For anautogenous mosquito species, like Ae. aegypti, newly emerged adult females neither respond to host odors nor engage in blood-feeding; the bases for these behaviors are poorly understood. Here we investigated detection of two components of an attractant blend emitted by vertebrate hosts, octenol and CO2, by female Ae. aegypti mosquitoes using electrophysiological, behavioral, and molecular approaches. An increase in sensitivity of octenol olfactory receptor neurons (ORNs) was correlated with an increase in octenol-mediated attractive behavior from day 1 to day 6 post emergence. While the sensitivity of octenol ORNs was maintained through day 10, behavioral responses to octenol decreased as did the ability of females to discriminate between octenol and octenol + CO2. Our results show differing age-related roles for the peripheral receptors for octenol and higher order neural processing in the behavior of female mosquitoes.